Design and development of icephobic coatings based on sol-gel/modified polyurethane paints. (December 2020) - Carreño, F.; Gude, M.R.; Calvo, S.; Rodriguez de la Fuente, O.; Carmona, N.
Graphical abstract: Abstract: In the present study, a coating with icephobic properties has been developed based on an easy two-step fabrication process. The coating is free from fluorides and nanoparticles. The procedure is easy, adequate for large scale applications and uses environmentally friendly low-cost raw materials. It has been applied on carbon fiber/epoxy resin composite panels, but it could be extended to other kind of surfaces. The structure of the coating has been prepared by the modification with PDMS of a commercial polyurethane paint as a first step. The second step involves the preparation of a hybrid sol-gel that is deposited on the polyurethane paint modified with PDMS forming a heterogeneous film of isolated solid droplets. The results show a reduction of the adhesion force of the ice up to 80 %. Properties like roughness, water contact angle and ice adhesion tests have been measured for more than 100 shear-off/freezing ice cycles. The evolution of the surface during the cycles has been monitored and it shows a modification process reported in the manuscript. This icephobic coating is a promising candidate to protect surfaces in different industrial sectors where other systems against ice accumulation cannot be easily employed.